2014
DOI: 10.1007/s12160-014-9642-7
|View full text |Cite
|
Sign up to set email alerts
|

Recommending Self-Paced Exercise among Overweight and Obese Adults: a Randomized Pilot Study

Abstract: Background: National guidelines call for exercise of at least moderate intensity; however, recommending self-paced exercise may lead to better adherence, particularly among overweight and obese adults. Purpose: Test proof-of-concept for recommending self-paced exercise among overweight adults. Methods: Fifty-nine healthy, low-active (exercise <60 min/week), overweight (Body Mass Index: 25.0-39.9) adults (18-65) received a six-month print-based exercise promotion program with the goal of walking 30-60 min/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 17 publications
2
37
0
1
Order By: Relevance
“…This finding is consistent with previous research documenting the effects of self-selected vs. imposed intensity on PA (Ekkekakis et al, 2008(Ekkekakis et al, , 2011Hamlyn-Williams et al, 2014;Rose & Parfitt, 2012;VazouEkkekakis & Ekkekakis, 2009) and work suggesting that this "at risk" group may benefit specifically from an affect-based exercise prescription (Ekkekakis & Lind, 2006;Ekkekakis et al, 2010). Moreover, the findings add to the growing body of evidence (Parfitt et al, , 2015Williams et al, 2015) supporting the use of affective factors as a primary method of exercise prescription (Garber et al, 2011). However, the novel finding we report here extends previous research in demonstrating that the positive effect of an affect-guided prescription on PA is specific to those individuals for whom PA is more likely to be experienced as affectively unpleasant (i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with previous research documenting the effects of self-selected vs. imposed intensity on PA (Ekkekakis et al, 2008(Ekkekakis et al, , 2011Hamlyn-Williams et al, 2014;Rose & Parfitt, 2012;VazouEkkekakis & Ekkekakis, 2009) and work suggesting that this "at risk" group may benefit specifically from an affect-based exercise prescription (Ekkekakis & Lind, 2006;Ekkekakis et al, 2010). Moreover, the findings add to the growing body of evidence (Parfitt et al, , 2015Williams et al, 2015) supporting the use of affective factors as a primary method of exercise prescription (Garber et al, 2011). However, the novel finding we report here extends previous research in demonstrating that the positive effect of an affect-guided prescription on PA is specific to those individuals for whom PA is more likely to be experienced as affectively unpleasant (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The promising findings from this pilot trial are consistent with similar studies that have shown the benefits of regulating exercise intensity using affect or perceived exertion (Parfitt et al, , 2015Williams et al, 2015) and add to the evidence base supporting the use of affect as a primary mode of exercise prescription. Overall, the study indicated the importance of the way in which PA is prescribed to inactive adults, with particular attention to matching the prescription to the level of CRF of the individual.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Williams and colleagues’ recent paper [1], Recommending self-paced exercise among overweight and obese adults: A randomized pilot study , extends research demonstrating positive associations between self-paced exercise and affective responses to, and perceived autonomy for exercise [24]. The authors found that low-active participants assigned to a self-paced walking prescription walked significantly more minutes per week than participants assigned to a moderate-intensity walking prescription.…”
mentioning
confidence: 89%
“…Instead of prescribing moderate intensity exercise for a minimum of 150 minutes per week, perhaps we ought to encourage people to “do what feels good.” But, before we throw the exercise prescription baby out with the bathwater, note that just two weeks into the Williams et al study, participants in both conditions were already falling short of the goal to walk 150 minutes per week [1]. By six weeks, participants walked only 50% of this goal on average.…”
mentioning
confidence: 99%